Penerapan Metode AHP dan TOPSIS sebagai Sistem Pendukung Keputusan untuk Pemilihan Laptop Baru dan Bekas sebagai Media Penunjang Pembelajaran Masa dan Pasca Pandemi COVID-19 - Mohammad Aditya Noviansyah; Imam Cholissodin; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
During pandemic period student requires to receive online education because of government regulations to limit activities outside home. Online learning support media such as laptops, mobile phones and computers need to be owned to run online education. These problems have resulted in the need for online learning support devices that continues to grow, including the sale of laptops. Laptops have various specifications, differences in specifications in laptops will affect the function of their use. During the pandemic, students on average use laptops for office application and attending online classes which require low specifications. In addition, laptops are also used by them for graphic design or for gamers, which requires high specifications to meet their needs. To buy a laptop according to user needs, user need an expert to get the optimal laptop recommendation according to user needs. Problems in choosing the optimal laptop according to needs can be solved with a Decision Support System (DSS), which is known as a branch of science in operations research that can be used as decision support in a mathematical model. In this research, the method of Analythical Hierarchy Process and Technique for Order Preference by Similiarity to Ideal Solution are the methods chosen for decision making. The results of the implementation of laptop selection recommendations with the AHP and TOPSIS methods obtained an accuracy of 99.85%. Changes in accuracy can be affected by the paired criteria entered and the minimum specification laptop entered by the user.